PEMIKIRAN HUKUM ISLAM BIDANG PERHAJIAN: (Manajemen, Politik, Ekonomi) - Nurul Azizah; Abd. Halim Talli; Kurniati Kurniati (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
The implementation of the pilgrimage in the mid-19th century experienced a significant increase. Various purposes and activities they do while in the holy land. Hajj is a means of communication between a servant and his Creator. This worship was first prescribed in the sixth year of the Hijrah. The word al-Hajj according to language means intentional. Therefore, according to the term Islamic shari'a, it means deliberately visiting the Ka'bah in Mecca to perform several series of acts of worship according to the pillars and conditions that have been determined by syara'. Hajj is the fifth pillar of Islam and the fourth point of worship, which is ordered after the three previous points of worship are prescribed, namely: prayer, fasting in Ramadan, and zakat. Hajj has many roles and many benefits. This study is examined by looking at the contribution of the Hajj in various social fields that occur after performing the worship for the people in Indonesia.